Gender inequality in sports - Moawad, J. (Fair Play. Revista de Filosofía, Ética y Derecho del Deporte, 2019)
This paper describes the vast differences in earnings between men and women in sports, the historical roots for this and the current causes. It claims that wage differences between men and women are unjust and that governments and sports organizations ought to rectify this and offer equal opportunities for both genders. It proposes numerous corrective schemes and provides answers to several objections.